Being a woman leader: Informal personal networks and leadership identity construction in A Confucian culture - HOANG, Lan Anh (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, the perception on leadership has been different from traditional ones that used to align to agentic characteristics. However, for the top of mind, people normally think about masculine characteristics when referring to leadership concept. It could be so disadvantageous for women leaders that they can be trapped in the line between two perspectives: one for their nature characteristics, one for their changes to be suitable for stereotypical definitions of leadership characteristics. However, with both, they still face to “labyrinth” metaphor during their leadership journeys. The solution of using informal personal networks to construct women’s leadership identity has called much attention of scholars working in women leadership and leadership identity construction with the aim to find effective ways to enhance women’s advancement. The new perception on leadership identity as value creation and the reciprocal relationship between informal personal networks and leadership identity construction have been contended as emerging solutions for women leadership.